Excitonic properties of ZnS quantum wells in ZnMgS - Urbaszek, B; Townsley, C; Tang, X; Morhain, C; Balocchi, A; Prior, K; Nicholas, R; Cavenett, B (2002)
The excitonic properties of cubic ZnS quantum wells in ZnMgS are studied by reflectivity and magneto-optics. A remarkable improvement in the quality of the samples grown by MBE on Gal? substrates has allowed the observation of heavy and light hole exciton transitions with values for the FWHM as narrow as 5 meV The 2s state of the heavy hole exciton is identified and exciton binding energies as high as 55 meV are deduced, indicating that for quantum wells narrower than 3.5 nm the exciton-LO phonon scattering can be suppressed. Zeeman splittings; of the order of 10 meV for both the light and heavy hole exciton transitions appear in magneto-reflectivity spectra in magnetic fields up to 54 T. Large light hole exciton g-values of the order of four for all quantum wells are obtained due to the light hole being the uppermost valence band in these tensile strained quantum wells. A strong reduction in the diamagnetic shifts for narrow wells is observed due to increasing quantum confinement.